PENGARUH FAMILY CONTROL DAN FOREIGN OWNERSHIP PADA PELAPORAN KEUANGAN DI INTERNET - Nenggalih Paksi Kumara (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2015)
This study aims to analyze and to obtain empirical evidence about the influence of family control and foreign ownership on the reporting of financial information on the internet. This study differs from other studies due to the regulation of BAPEPAM-LK, which requires companies to upload their financial information the website of company. Apart from two main variables, this study also examines the effect of several control variables such as company size, profitability and leverage. In this study internet financial reporting is measured by using an index of disclosure consists of 78 items. Samples procedures in this study is purposive sampling method that produces a sample 140 companies listed on the Stock Exchange in 2014. The method of data analysis of this study is multiple linear regression analysis. These results indicate that family control and size have a positive and significant association with internet financial reporting. On the other hand, foreign ownership, profitability and leverage indicates insignificant association with internet financial reporting. Keywords: internet financial reporting, family control, foreign ownership